Peace Education as a Recipe for Terrorism in West Africa. - Adetoro, Rasheed Adenrele (Advances in Social Sciences Research Journal, 2015)
Peace is a sine-qua-non for development all over the world. The current trend of terrorism reflects the need to deliberately teach culture of peace and tolerant attitude among youths. According to Ogunyemi and Adetoro (2013), the need to ‘catch them young’ to curtail culture of violence and aggressive behavours among the adolescents needs urgent attention. Most nations in West Africa had witnessed and are still witnessing several political, religious, socio-cultural and ethnic-related conflicts that have claimed many lives and properties in the last three decades. Prominent among these is the rampaging Boko Haram insurgency that has claimed over 15,000 lives since 2009 with more than 300 schools damaged or destroyed and over 800,000 children displaced in North Eastern Nigeria (UNICEF, 2015). This worrisome trend calls for new strategies to promote peace culture through education. This is why UNESCO (1998) canvassed that Peace Education should be taught as a veritable means of promoting necessary attitudinal change to evolve a culture of peace and non-violence behaviour. This paper therefore intends to explore the various theoretical background that are relevant to behaviour modification like Bandura (1976) social learning theory; Jenkins (2006) and Kester (2007) pedagogies of engagement theory. These theoretical frameworks were used to justify Learning Together and Constructive Controversial classroom engagements for attitudinal transformation against terrorism. With copious evidences, the various multi-track peace education approaches like tolerant sociometry, and Reciprocal Peer Relations Conditional Learning (RPRCL) were recommended to form parts of the curricula recipe to stem the rising tide of terrorism in West Africa. Good governance was also suggested to be the pillar for the peace education curricula rescue.